Penggunaan Media Pembelajaran Film Animasi Pada Mata Pelajaran Bahasa Jawa Untuk Meningkatkan Keterampilan Menyimak Siswa Kelas IV SDN 1 Garunglor - Wildan Adib Furqon; Nasokah Nasokah; Sofan Rizqi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to: (1) examine how animated films are used as a learning medium for Grade IV students at SD N 1 Garunglor in learning the Javanese language; (2) determine students' initial listening comprehension skills before the implementation of animated film media; (3) assess how animated films can improve students' listening skills in Javanese language. This research employed a quantitative approach with an experimental method using a One-Group Pretest-Posttest Design. Data collection instruments included observation, interviews, tests, and documentation. The findings indicate that the use of Javanese-language animated films is effective in improving the listening skills of Grade IV students. Prior to the intervention, students' listening skills were relatively low with a pre-test average of 53.5, and most did not meet the Minimum Mastery Criteria (KKM). After the intervention, the post-test average rose to 80.5 with a mastery rate of 87.5%. The t-test results showed t-value (6.494) > t-table (2.364) with p-value 0.000336 < 0.05, indicating a statistically significant difference. The N-Gain score of 0.57 (moderate category) confirms that animated film media is reasonably effective in enhancing students' listening skills in Javanese language learning.